DIGITAL TRANSFORMATION OF ACCOUNTING THROUGH ARTIFICIAL INTELLIGENCE TECHNOLOGY - Rohaeni Marliana; Audy Dea Maharani; Rina Destiana (Yayasan Adra Karima Hubbi, 2026)
Artificial intelligence (AI) has played a crucial role in improving the efficiency and accuracy of financial data management in the accounting field through process automation, big data analysis, and faster and more precise decision-making. This research aims to analyze the perception of accounting students in Indonesia towards the application of artificial intelligence (AI) in the digital transformation of accounting. Using a descriptive quantitative method with a survey of 163 respondents, the results showed that the majority of students understood that AI has been applied in companies and got information from the internet and social media. They agree that AI can automate routine tasks, increase efficiency, and minimize errors in the accounting process. However, the study also revealed concerns regarding potential workforce reductions, over-reliance on technology, and data security risks and skills gaps that could exacerbate social inequality. These findings highlight the importance of improving student competencies and attention to social, ethical, and security aspects in the application of AI so that its benefits can be utilized optimally and responsibly in the digital era.